A Thematic Review of the Models of ICT Integration in Tracking Malaria Drug Administration in Ugandan Health Units. - Ssegawa, E. James Kiggundu; Kimwise, Alone (Student's Journal of Health Research Africa, 2022)
Background This study aimed at reviewing models propounding thematic linkage to system integration of ICT transaction processes that inform tracking administration of malaria drugs in health units in Uganda. Methods The study engaged structural and thematic review approaches for narrative and meta-synthesis of literature analysis to cite, make comparisons, and contrast including criticisms of directed stimulation of information-oriented integration, process-oriented integration, service-oriented Integration, user-oriented integration, and other success drivers of the need for ICT integrations. Comparisons of models by case analysis qualified a structured proposition of development of the model for tracking the administration of Malaria drugs in health units. Scope Integration review was guided by the Enterprise Application Integration solution model, Model Driven Integration Approach, Technology Transfer of Reference, DeLone & McLean IS Success Model among others, focusing on the stimulation of information, processes service and user-oriented integrations, valid ability, technology context, ease of use, scalability, flexibility, and trainability as success drivers. Findings Studies on integration and IC-enabled development reveal that ICT is widely accepted, and its crucial functions increase efficiency, cost-effectiveness, and competitiveness. Failure of integration of ICT in developing countries has a positive relationship with lack of awareness, management commitment, defined ICT based-roles as tools rather than solutions for organizational transformation, responsiveness to vision and mission goals, systemic methods of implementation, system ownership, and poor policy and planning. Conclusion Integration of Information Communications Technology in health units is a major driver of information, processes, service, and user-oriented transactions for effective service provision and delivery in Uganda. Technology Context has a negative but linear correlation on ease of use (Intension and Actual) of ICTs (B = - 0.087) and negatively influences the same (β= - 0.050). The intention and actual use of Technology Context in tracking drug administration is influenced by the ability of application of the users.